Antecedents of self-care in adults with congenital heart defects. (15th December 2015) - McCabe, Nancy; Dunbar, Sandra B.; Butler, Javed; Higgins, Melinda; Book, Wendy; Reilly, Carolyn
Abstract: Background: Adults with congenital heart defects (ACHD) face long-term complications related to prior surgery, abnormal anatomy, and acquired cardiovascular conditions. Although self-care is an important part of chronic illness management, few studies have explored self-care in the ACHD population. The purpose of this study is to describe self-care and its antecedents in the ACHD population. Methods: Persons with moderate or severe ACHD (N = 132) were recruited from a single ACHD center. Self-care (health maintenance behaviors, monitoring and management of symptoms), and potential antecedents including sociodemographic and clinical characteristics, ACHD knowledge, behavioral characteristics (depressive symptoms and self-efficacy), and family-related factors (parental overprotection and perceived family support) were collected via self-report and chart review. Multiple regression was used to identify antecedents of self-care maintenance, monitoring, and management. Results: Only 44.7%, 27.3%, and 23.3% of participants performed adequate levels of self-care maintenance, monitoring and management, respectively. In multiple regression analysis, self-efficacy, education, gender, perceived family support, and comorbidities explained 25% of the variance in self-care maintenance (R 2 = .248, F(5, 123) = 9.44, p < .001). Age, depressive symptoms, self-efficacy, and NYHA Class explained 23% of the variance in self-care monitoring (R 2 = .232, F(2, 124) = 10.66, p < .001). Self-efficacy and NYHA Class explained 9% of the variance in self-care management (R 2 = .094, F(2, 80) = 5.27, p = .007). Conclusions: Low levels of self-care are common among persons with ACHD. Multiple factors, including modifiable factors of self-efficacy, depressive symptoms, and perceived family support, are associated with self-care and should be considered in designing future interventions to improve outcomes in the ACHD population.